Comparative Mapping and Candidate Gene Analysis of SSIIa Associated with Grain Amylopectin Content in Barley (Hordeum vulgare L.) - Fan, Xiangyun; Zhu, Juan; Dong, Wenbin; Sun, Yuandong; Lv, Chao; Guo, Baojian; Xu, Rugen (Frontiers in Plant Science, 2017)
Amylopectin concentration in barley endosperm has important effects on grain quality and end-use. In this study, quantitative trait locus (QTL) analysis together with genome-wide association studies (GWAS) were performed to identify markers linked to grain amylopectin content respectively using a doubled haploid (DH) population of 178 lines and a collection of 185 diverse barley germplasms both genotyped by genotyping-by-sequencing (GBS). A stable QTL on chromosome 7H and eleven associated single nucleotide polymorphisms (SNPs) were detected. The SSⅡa (SSⅡ-3) gene was located in the co-localized region and could be a candidate gene. Subsequent characterization of SSⅡa alleles of two parents of the DH population revealed that a 33-bp deletion in exon 2 is responsible for the reduction of SSⅡa transcript, leading to a lower expression level thus a lower amylopectin content. A sequence-based genetic marker was designed for the SSⅡa allele and could be effectively used in barley breeding programs.